Characterization of the Viscoelastic Properties of Ovarian Cancer Cells Membranes by Optical Tweezers and Quantitative Phase Imaging - Lu, Thompson; Anvari, Bahman (Frontiers in Physics, 2020)
Ovarian cancer is the deadliest gynecological cancer in women. It is a highly metastatic disease with pelvis, regional lymph nodes, and peritoneal cavity as major sites for tumor deposits. Mechanical properties of ovarian cancer cells can play a major role in metastasis as the cells detach from the ovaries and undergo deformation during the metastatic process. Herein, we have characterized the viscoelastic properties of the plasma membrane of normal epithelial (IOSE364) and cancerous (SKOV3) ovarian cells by optical tweezers and quantitative phase imaging (QPI). Using optical tweezers, we obtained time-resolved force profiles associated with membrane tethers pulled from the cells. We used QPI to measure the diameter of membrane tethers, and subsequently, estimated the membrane bending modulus and membrane tension in the tether. Our results indicate that the force (350 ± 81 pN) (mean ± standard deviation) required to separate the membrane of SKOV3 cells from the cytoskeleton was significantly lower (p=0.0004) than the force (190 ± 76 pN) for IOSE364 cells. The mean stiffness (2.8 ± 0.8 pN/µm) of membrane tethers pulled from SKOV3 cells was significantly lower (p=0.032) than the value for IOSE 364 cells (3.7 ± 0.8 pN/µm). Mean value of the force relaxation characteristic time associated with diffusive flow of lipids was also significantly lower (p=0.018) for SKOV3 membranes (12.9 ± 6.9 s) as compared to the value for IOSE 364 membranes (20.4 ± 6.2 s). Similarly, the mean value of the membrane bending modulus for SKOV3 cells ((0.51 ± 0.23) x 10-18 J) was significantly lower (p=0.007) than the value for IOSE364 cells ((1.29 ± 0.32) x 10-18 J). Overall, our results suggest that the membranes of SKOV3 cells are less resistant to mechanical deformation. Increased membrane susceptibility to mechanical deformation may be a facilitating factor in the metastatic behavior of cancerous ovarian cells. Characterization of membrane biomechanics may provide a useful diagnostic biomarker for assessment of the metastatic potential of ovarian cancer, and a target for development of therapeutics.